Efektivitas Pengembangan Bahan Ajar Seni Budaya Melalui Aplikasi Kinemaster di Masa Pandemi Covid-19 - Winarsih Winarsih; Moh Rusnoto Susanto; Dwi Susanto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
The COVID-19 pandemic (Coronavirus disease 2019) is an epidemic that has changed various aspects of human life, especially related to the world of education. Therefore, the purpose of this study was to determine the effectiveness of developing cultural arts teaching materials during the COVID-19 pandemic, especially for class XI SMA Muhammadiyah Ponjong in arts and culture subjects. The research method uses mixed methods the research, with a sequential exploratory design approach. The use of the population and the sample is class XI SMA. For data collection techniques, they are using observation, interviews, and questionnaires via a google form. Then, for data analysis techniques using statistical data in the form of diagrams. Moreover, the results of this study regarding the use of the KineMaster application is an innovation where no teacher has ever used the development of similar teaching materials in the teaching process. With this KineMaster application, teachers can explain the material that is based on theory and practice. In addition, although distance learning, teachers can still meet face-to-face behind the scenes.Keywords : kinemaster application, pandemic, learning outcomes, cultural arts subject